การปรับปรุงผิวรัตนโลหะที่มีไทเทเนียมเป็นส่วนประกอบหลัก โดยกระบวนการทางกล เพื่อประยุกต์ใช้ในงานทันตกรรมรากฟันเทียม - สุภารัตน์ อุดมเลิศปรีชา (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Ti-based bulk metallic glass (BMG) is a new class of titanium alloys that exhibits excellent properties for biomedical applications such as bone plates, and dental implants, etc. They have high strength, low elastic modulus, good corrosion resistance and satisfactory biocompatibility. Titanium alloy cylindrical rod with a nominal composition of the Ti40Zr10Co36Pd14 were fabricated by arc-melting and casting into copper mold to be used plasma cathode in filtered cathodic vacuum arc (FCVA) deposition technique. The Ti-6Al-4V alloy was studied in parallel as a control material. This new Ti-based metallic glass (MG) composition has shown promising osteoblast-biocompatible characteristics, no cytotoxicity on MC3T3-E1 cells and SaOS-2 cells. Afterwards, coin-shape samples of the Ti40Zr10Co36Pd14 with a diameter of 15 mm and thickness of 1 mm were prepared by arc-melting and casting into copper mold. The coin-shape samples were polished, and then followed by blasting with 50 µm and 250 µm average particle sizes of alumina. The larger size of alumina particle, the higher the Ra, Rq and Rt with significant difference. When using the same size of alumina, the blasted Ti40Zr10Co36Pd14 sample showed lower roughness values than those blasted Ti-6Al-4V samples. This may be because of the higher hardness values of Ti40Zr10Co36Pd14 sample, when compared to the softer Ti-6Al-4V samples. Some abrasive alumina particles were found to be embedded onto the blasted surface. The actin cytoskeleton of MC3T3-E1 on Ti40Zr10Co36Pd14 and Ti-6Al-4V samples using immunofluorescence micrographs indicated that cells could attach very well on all samples. Cell attached on blasted Ti40Zr10Co36Pd14 samples faster than those untreated samples. The cytoskeleton of MC3T3-E1 on untreated Ti-6Al-4V samples changed to flat and elongated shape which was similar to fibroblast cell shape but blasted Ti-6Al-4V samples could maintain osteoblast-like cell shape.